The male teacher shortage in secondary public schools in Azerbaijan : Why some males work in public schools while most do not choose teaching as a career path - Rasulova, Ulker (ADA University, 2022)
The purpose of this qualitative study was to explore and understand the factors that lead to the male teacher shortage along with the factors that motivate males to become teachers in public schools in Azerbaijan. This study addressed what affected men’s career decisions, what would dissuade men from becoming secondary school teachers, and how important is it to have male teachers in secondary public schools. A semi-structured approach was employed to interview 16 male, 20 female teachers, 4 education experts, 2 sociologists, a psychologist, 4 school principals and 10 male university students studying teaching in an effort to understand the shortage of male teachers. Results indicated that despite male teachers have a strong desire and are passionate to work as teachers in secondary public schools, there are factors such as diminished prestige of teaching, low salary, and feminization of the profession that deter men from pursuing a career in teaching. Further, serving as a male role model for students was significant, since they considered filling the void left by absentee fathers. This study provided a review of existing literature, the results of interview, responses to research questions, discussed limitations, and made recommendations for further research.
Keywords: Schools, Secondary.; Schools, Public.; Gender imbalance.; Education